The Structural Geology Constellation of Western Boundary of Yogyakarta Basin - Widagdo, Asmoro (Departemen Teknik Geologi, 2019)
The Yogyakarta Basin is located on the south-side of the central part of Java Island which is located on the active tectonic boundary from the Tertiary to Quaternary periods. Kulonprogo volcanic mountains and South Serayu folds are in the west of the Yogyakarta basin. To the east of the Yogyakarta basin is found the Southern Mountains of eastern Java. The western boundary of the Yogyakarta Basin has typical types of geological structures. This research was conducted to study the type of geological structure that is the western boundary of the Yogyakarta Basin. The study was conducted through a series of field work to collect geological structure data such as bedding-plane of sedimentary rocks, joint planes, fault planes, fault types, folds, and then field data analysis was performed using stereographic methods. The main geological structure, which is the western boundary of the Yogyakarta Basin, is the synistral fault with the type of left-stepping left lateral fault associated with subduction in the south of Java. This structure of the major synistral fault produces companion faults in the form of dextral faults, synistral faults, normal faults, shear joints and extension joints. The other geological structures, originating from different sources, are related to the influence of forces from the east of the Yogyakarta Basin. This structure forms thrust fault, fold, dextral fault, synistral fault, shear joints and extension joints.